Three Years After Black Saturday: Long-Term Psychosocial Adjustment of Burns Patients as a Result of a Major Bushfire. Issue 3 (May 2016) - Pfitzer, Birgit; Katona, Lynda Jane; Lee, Stuart J.; O'Donnell, Meaghan; Cleland, Heather; Wasiak, Jason; Ellen, Steve
Abstract : Despite increasing evidence that burn injuries can result in multiple psychological sequelae, little is known about the long-term psychosocial adjustment to burns sustained in a major bushfire. The aim of the present study was to assess long-term psychological distress and health-related quality of life in Australian burns patients as a result of the 2009 Black Saturday bushfires. Eight male and five female burns patients with a mean age of 53.92 (SD = 11.82) years who received treatment at a statewide burns service participated in the study. A battery of standardized questionnaires was administered to assess general psychological distress, burns-specific and generic health-related quality of life, alcohol use, and specific psychological symptoms of posttraumatic stress disorder, depression, and anxiety. The results revealed that more than 3 years after Black Saturday 33% of the burns patients still suffered "high" to "very high" levels of general distress, whereas 58% fulfilled partial or full criteria for posttraumatic stress disorder. Furthermore, participants still experienced significantly impaired physical health functioning as compared to their preinjury status including limitations in work-based activities, increased bodily pain, and lower vitality overall. The trajectory of distress varied for participants. Some individuals experienced little distress overall, whereas others displayed a decline in their stress levels over time. Notwithstanding, some patients maintained high levels of distress throughout or experienced an increase in distress at a later stage of recovery. The results point to the importance of psychosocial screening to identify distress early. Follow-up assessments are crucial to diagnose individuals with chronic or late onset of distress.